Chemoradiotherapy with 3-weekly CDDP 80 mg/m2 for head and neck squamous cell carcinoma: 5-year survival data from a phase 2 study - Otaki, Kohei; Takahashi, Takeshi; Tanaka, Ryoko; Saijo, Kohei; Omata, Jo; Yokoyama, Yusuke; Shodo, Ryusuke; Ueki, Yushi; Yamazaki, Keisuke; Ota, Hisayuki; Togashi, Takafumi; Takahashi, Nao; et al. (Frontiers in Surgery, 2022)
Objective The global standard for chemoradiation therapy (CCRT) for head and neck squamous cell carcinoma is cisplatin 100 mg/m2 administered once every three weeks, although cisplatin 80 mg/m2 is also widely used as an alternative treatment to reduce adverse events in Japan. We aimed to assess the long-term survival outcomes and late adverse events associated with CCRT with a 3-weekly cisplatin dose of 80 mg/m2. Methods A phase 2 study on CCRT with a 3-weekly cisplatin dose of 80 mg/m2 was performed in 47 patients between April 2015 and December 2016 at four centers in Japan. Survival outcomes and late adverse events at 5 years after this phase 2 trial were investigated. Results The median follow-up period was 61 months. The 5-year progression-free survival/overall survival of all 47 patients was 66.0%/76.6%, while that of patients with stage III, IV disease (UICC) was 65.6%/71.9%. Seventeen patients (36%) experienced dysphagia as a late adverse event. Univariate and multivariate analyses revealed a significant association between acute mucositis/low body mass index (BMI) during CCRT and late dysphagia. Conclusion The survival outcomes of CCRT with a 3-weekly cisplatin dose of 80 mg/m2 may be comparable to the previously reported dose of 100 mg/m2. Acute mucositis and low BMI at CCRT were risk factors for late dysphagia, indicating the importance of managing these conditions during CCRT to prevent late adverse events. Caution and care for acute mucositis and swallowing training in patients with low BMI may be important for preventing late-stage dysphagia.